Analisis Sosiolinguistik Bentuk Sapaan dalam Film Agak Laen Karya Muhadkly Acho - Aryalita, Made Karla (Kajian Linguistik dan Sastra, 2026)
This study analyzes the forms of address from a sociolinguistic perspective in the film Agak Laen by Muhadkly Acho. This study uses the theories of Kridalaksana and Ervin-Tripp to analyze the data obtained by descriptive qualitative methods with the listening-noting technique. The results of the study are presented through formal and informal methods. The results of the study show that the forms of address in this film are influenced by several elements, such as personal pronouns, proper names, kinship terms, titles and ranks, N (Nominal)+ku, situations, ranks, identity devices, and generation levels which are the relationship between Kridalaksana's theory of address forms in Indonesian and Ervin-Tripp's theory of address forms in American English. The use of address forms is also influenced by the situation, gender, and age which are the background factors for the use of address forms in society. From a sociolinguistic perspective, the results of the study show that the greatest influence on the use of address forms in Indonesia is social and linguistic variation in society. Abstrak Penelitian ini menganalisis bentuk-bentuk sapaan dari segi sosiolinguistik yang terdapat dalam film Agak Laen karya Muhadkly Acho. Penelitian ini menggunakan teori Kridalaksana dan Ervin-Tripp untuk menganalisis data yang diperoleh dengan metode kualitatif deskriptif dengan teknik simak-catat. Hasil penelitian disajikan melalui metode formal dan informal. Hasil penelitian menunjukkan bahwa bentuk sapaan dalam film ini dipengaruhi oleh beberapa unsur, seperti kata ganti orang, nama diri, istilah kekerabatan, gelar dan pangkat, N (Nominal)+ku, situasi, pangkat, perangkat identitas, dan tingkat generasi yang merupakan keterkaitan teori bentuk sapaan Kridalaksana bahasa Indonesia dan teori bentuk sapaan Ervin-Tripp bahasa Inggris-Amerika. Penggunaan bentuk sapaan juga dipengaruhi oleh situasi, jenis kelamin, dan usia yang menjadi faktor latar belakang penggunaan bentuk sapaan dalam masyarakat. Dari segi sosiolinguistik, hasil penelitian menunjukkan bahwa pengaruh terbesar penggunaan bentuk sapaan di Indonesia adalah variasi sosial dan bahasa dalam masyarakat.